2011
DOI: 10.1017/s0033291711000602
|View full text |Cite
|
Sign up to set email alerts
|

Daily cortisol, stress reactivity and psychotic experiences in individuals at above average genetic risk for psychosis

Abstract: Findings support altered HPA axis activity in individuals at above average genetic risk for psychotic disorder, as evidenced by higher diurnal cortisol levels and increased cortisol reactivity to daily stress. Results also suggest a dynamic association between cortisol secretion and the intensity of psychotic-like experiences and negative emotions in daily life, although the direction of this association remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
148
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 51 publications
10
148
2
1
Order By: Relevance
“…5,13 Previous studies have found elevated emotional reactivity to minor stressors in individuals with psychotic disorder and increased familial or psychometric risk (ie, a high score of sub-clinical PE). [12][13][14][15][16] Similarly, a recent study reported elevated emotional reactivity in response to minor stressors in individuals with an at-risk mental state (ARMS). 17 Previous research further suggest some degree of specificity, for example, of elevated emotional reactivity to social but not event-related stress as a putative mechanism underlying the association between childhood trauma and psychosis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,13 Previous studies have found elevated emotional reactivity to minor stressors in individuals with psychotic disorder and increased familial or psychometric risk (ie, a high score of sub-clinical PE). [12][13][14][15][16] Similarly, a recent study reported elevated emotional reactivity in response to minor stressors in individuals with an at-risk mental state (ARMS). 17 Previous research further suggest some degree of specificity, for example, of elevated emotional reactivity to social but not event-related stress as a putative mechanism underlying the association between childhood trauma and psychosis.…”
Section: Introductionmentioning
confidence: 98%
“…[8][9][10][11][12] Recently, the interplay between affective disturbances and stressful contexts and experiences in daily life (including stressful events, activities, and social situations) that may be underlying the development of PE has received much attention. [12][13][14][15][16] It has been repeatedly suggested that emotional reactivity to such routine daily hassles and minor socioenvironmental stressors may be an important mechanism. 5,13 Previous studies have found elevated emotional reactivity to minor stressors in individuals with psychotic disorder and increased familial or psychometric risk (ie, a high score of sub-clinical PE).…”
Section: Introductionmentioning
confidence: 99%
“…13,15 A number of studies have reported elevated emotional reactivity to minor stressful events, activities, and social situations in individuals with enduring psychosis and in those with higher familial or psychometric risk. [17][18][19][20][21] Two studies in individuals at ultra high-risk (UHR) of developing psychosis, 22,23 reported greater emotional reactivity to minor activity-related and social stress in this group. 24,25 Findings from the only study conducted to date in individuals with first-episode psychosis (FEP), 25 which allowed to minimize the impact of illness chronicity, 20,24 further suggests that elevated stress sensitivity is associated with an increased intensity of psychotic experiences in FEP individuals, UHR individuals and controls, and this association is greatest in FEP individuals.…”
Section: Ecological Interventionist Causal Models In Psychosis Putatimentioning
confidence: 99%
“…We used data from six different studies 10,[26][27][28][29] (see table S1 in the supplementary materials for in-and exclusion criteria of these studies) that used a similar ESM protocol. Participants were classified either as (i) 'healthy' control individuals (i.e.…”
Section: Samplesmentioning
confidence: 99%